Development of luminescence dating methods in tectonically active settings: dating seismic related fanglomerates in alluvial fans located in Coachella Valley, southern California - Ataee, Nina (Kansas State University, 2019)
In tectonically active arid and semi-arid regions like southern California, alluvial fans and their drainages record not only paleoenvironmental change but also fault movement. To be able to decipher this precious information, a suitable chronological method is required. For events occurring over Late Quaternary timescales, optically stimulated luminescence (OSL) dating is a chronological method that can be used in these settings; however, current OSL approaches are only suited to the fine sand deposits which are present as layers or lenses in the fan architecture. The problem with this sampling approach is that in many fan exposures such deposits are rare, limiting the applicability of OSL. In this study we have investigated the feasibility of a luminescence method for dating fanglomerates by sampling the coarse fraction and extracting the fine sand matrix for dating. Regarding this new approach, issues of partial bleaching and gamma dose-rate heterogeneity should be carefully considered; yet this is worthwhile since this method can greatly expand the applicability of OSL dating in similar settings. We found that quartz in our sampling area is dim and has poor OSL characteristics, therefore, no ages are calculated based on quartz OSL. On the other hand, K-rich feldspar infrared stimulated luminescence (IRSL) was bright with good characteristics. We also conducted single grain IRSL on three samples (two fanglomerates and a fine sand layer) to investigate the extent of partial bleaching and equivalent dose (De) overdispersion in fanglomerate-derived grains. The data were then modeled with finite mixture model (FMM) using the Luminescence software package in R, allowing us to separate different components in the data. Assessment of gamma dose-rate heterogeneity in the fanglomerate environment was carried out by splitting the fanglomerate samples into <2 mm and >2 mm size fractions, and comparing data from high-resolution gamma spectrometry and ICP -AES/-MS analyses of the size fractions. The two fanglomerate sample evaluation demonstrates that single grain analysis and finite mixture modeling (FMM) are essential for De assessment. Fanglomerate dose rate analyses by means of ICP -AES/-MS and high-resolution gamma spectrometry illustrate homogeneous environment for the <2 mm proportions of the samples; however, the >2mm proportions are indicative of dose rate heterogeneity probably due to different lithologies. Our results from twelve samples indicate that alluvial fan formation in the Coachella Valley happened during both glacial periods and transition from glacial to interglacial periods. In the San Bernardino site, our depositional ages are concordant with the TCN surface age of Owen et al. (2014), indicating fast fan deposition during the marine isotope stage (MIS) 4 (65 ± 10 ka). The paleosol layer (78.81 ± 8.04 ka) beneath this fluvial setting suggest that soil development occurred mainly during the interglacial period MIS 5. In the Indio Hills (north of Biskra Palms) site, almost all depositional ages lie within interglacial periods: MIS 3, MIS 5, MIS 9 and the Holocene. The calculated minimum slip rate along the Mission Creek fault in Indio Hills area based on the depositional age of sample MC1805 (~75 ka) is 7.0 ± 1.3 to 8.4 ± 1.4 mm/yr. This rate is smaller than the 12.2 to 21.7 mm/yr slip rate along the this fault at Biskra Palms (Behr et al., 2010). Since our OSL age provides a maximum age constraint (i.e. sediment deposition in the alluvial fan prior to offset) and hence a minimum slip rate, this rate could suggest that the slip rate along the Mission Creek fault is constant at least between Biskra Palms and Indio Hills. On the other hand, there is a possibility that the slip rate along the Mission Creek fault has slowed from the Biskra Palms toward the northwest and the slip might then have been transferred to the Banning fault.
Keywords: Optically stimulated luminescence; pIRIR; Alluvial fan; Mission Creek fault; Coachella Valley